PERANAN PERBANKAN PADA PENERAPAN GREEN BUSINESS DAN SUSTAINABILITY DEVELOPMENT - Diky Rahmansyah; Muhammad Iqbal fasa; Suharto (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2023)
Various things related to greening are increasingly becoming a trend in society. Starting from green labels, green products, green packaging, green consumers, green business, green banking, and so on. All of this is closely related to environmental management issues that have become market demands for environmental safety and sustainability. The greening movement is also happening in banking with the terminology